Modeling the Effect of Replacing Sugar-Sweetened Beverage Consumption with Water on Energy Intake, HBI Score, and Obesity Prevalence - Duffey, Kiyah J. (MDPI, 2016)
Sugar-sweetened beverages (SSB) contribute to excessive weight gain through added energy intake. Replacing SSB with water is one strategy that has shown promise in helping lower excessive energy intake. Using nationally representative data from US adults (n = 19,718) from NHANES 2007–2012 we examine the impact of replacing SSB with water on Healthy Beverage Index (HBI) scores and obesity prevalence. Replacing an 8-ounce serving of SSB with water lowered the percent of energy from beverages from 17% to 11% (among those consuming 1 serving SSB/day). Reductions in the percent energy from beverages were observed across all SSB consumption groups (1–2 servings/day and >2 servings/day). Among adults there was a 9% to 21% improvement in HBI score when one serving of water replaced one serving of SSB. Using previously published randomized controlled trials (RCT) and meta-analyses of measured weight loss we also predicted a reduction in the prevalence of obesity (observed: 35.2%; predicted 33.5%–34.9%, p < 0.05) and increase in the prevalence of normal weight (observed: 29.7%; high weight loss: 31.3%, p < 0.05). Our findings provide further epidemiologic evidence that water in the place of SSB can be used as a strategy to limit energy intake and help individuals meet beverage intake recommendations.